(untitled) (The Pakistan Development Review, 1970)
Over the past several years, the import-substitution strategy of develop¬ment has been examined in considerable detail by numerous economists. For the most part, these studies have been concerned with one or another side of this many-sided approach to development policy. It now seems useful to review this literature in an attempt to isolate major themes and arguments and to try to put together a cohesive and comprehensive picture of where we stand now. This paper is not intended as a summary of the individual articles and books on import substitution, but rather is aimed at bringing together the theoretical issues and the empirical results that not only are of interest in themselves, but which also seem to add up to something that might legitimately be called an approach to development. To do this, I asked three general questions: 1) what appears to be the essential mechanics of import substitution as it has been practised in various countries that have been investigated; 2) what problems have emerged, and why, as a consequence of the conventional import-substitution (IS) strategy; 3) what has been found that suggests or leads toward an alter¬native approach to development that incorporates the good and eliminates the bad of this conventional approach.